A study of change in occlusal contacts and force dynamics after fixed prosthetic treatment and after equilibration - Using Tekscan III - Reddy Chaithanya; Suresh Sajjan; A V Rama Raju (Wolters Kluwer Medknow Publications, 2019)
Aim: A study has been undertaken to evaluate the changes in occlusal force dynamics after conventional prosthetic rehabilitation. Materials and Methods: In Phase I, the preprosthetic phase, force distribution of 50% ± 10% on either sides of arch in maximum intercuspation and disclusion time (DT) <1 s during mandibular excursions was attained in all patients using Tekscan before starting prosthetic treatment. Conventional procedures to replace missing tooth by fixed dental prosthesis were carried out. Occlusal corrections were performed using articulating paper to the satisfaction of operator and patient. In Phase II, postprosthetic phase, 1 week after cementation of the fixed partial dentures, the occlusal force dynamics were rerecorded and evaluated using Tekscan. Any corrections required were done to restore the equilibrium. Occlusal perception of patient before and after equilibration was recorded by means of a standard questionnaire both in pre- and postprosthetic phase. Twenty patients requiring replacement of a single posterior missing tooth were selected. The obtained values were statistically analyzed using Student's t-test. Results: Subsequent to rehabilitation, the right-left balance of occlusal load was lost and DT was significantly increased. However, the subjective evaluation revealed no significant decline in occlusal comfort. Conclusion: Null hypothesis was rejected. Operator's assessment of articulating paper marks and patient's occlusal perception is not reliable in restoring occlusal equilibrium.